Stratospheric ozone depletion has contributed to the recent tropical La Niña-like cooling pattern - Yue Dong; Lorenzo M. Polvani; Yen-Ting Hwang; Mark R. England (npj Climate and Atmospheric Science)
Abstract Despite the continuous global warming, over the past several decades, the tropical East Pacific has experienced a cooling trend whose origin remains an area of active research. Mounting evidence has linked tropical sea-surface temperature (SST) patterns to changes in the Southern Ocean via remote teleconnections. Using a fully-coupled global climate model, we demonstrate that stratospheric ozone depletion can produce a La Niña-like tropical SST trend pattern resembling recent observations. This tropical response initially arises from mid-latitude ocean adjustments to ozone-driven surface wind anomalies, which then enhance in the tropics via positive cloud feedback and wind-evaporation-SST feedback. Our finding suggests that the observed La Niña-like tropical SST trend pattern may have been, in part, caused by the formation of the ozone hole in the late 20th century. It also implies that ozone recovery in the coming decades will likely contribute to a future weakening or reversal of the observed tropical SST trends.